Gods are watching and so what? Moralistic supernatural punishment across 15 cultures - Bendixen, Theiss; Lightner, Aaron D; Apicella, Coren; Atkinson, Quentin; Bolyanatz, Alexander; Cohen, Emma; Handley, Carla; Henrich, Joseph; Klocová, Eva Kundtová; Lesorogol, Carolyn; Mathew, Sarah; McNamara, Rita A; et al. (Evolutionary human sciences, 2023)
Psychological and cultural evolutionary accounts of human sociality propose that beliefs in punitive and monitoring gods that care about moral norms facilitate cooperation. While there is some evidence to suggest that belief in supernatural punishment and monitoring generally induce cooperative behaviour, the effect of a deity's explicitly postulated moral concerns on cooperation remains unclear. Here, we report a pre-registered set of analyses to assess whether perceiving a locally relevant deity as moralistic predicts cooperative play in two permutations of two economic games using data from up to 15 diverse field sites. Across games, results suggest that gods' moral concerns do not play a direct, cross-culturally reliable role in motivating cooperative behaviour. The study contributes substantially to the current literature by testing a central hypothesis in the evolutionary and cognitive science of religion with a large and culturally diverse dataset using behavioural and ethnographically rich methods.
Keywords: evolutionary and cognitive science of religion; free-list; cognitive anthropology; cultural evolutionary psychology; Behavioural economics